Colloidal LaPO4:Gd3+ nanocrystals: X-ray induced single line UV emission. Issue 47 (27th November 2018) - Espinoza, Sara; Juestel, Thomas; Haase, Markus
Abstract : X-ray excitation of LaPO4 :Gd 3+ nanocrystals results in single-line UV emission capable of activating organic molecules and enabling new biomedical applications. Abstract : Colloidal solutions of nearly monodisperse 5 nm LaPO4 :Gd 3+ nanocrystals are shown to strongly emit UV radiation upon excitation with tungsten Kα radiation (59.3 keV) or vacuum UV radiation (160 nm). The UV emission of the particles consists mainly of a single line at 311 nm corresponding to the 6 P7/2 – 8 S7/2 transition of Gd 3+ . The highest emission intensity is observed for LaPO4 nanocrystals with a Gd 3+ concentration of 20%. Since the absorption cross section of biomaterials is low for X-rays but high for 311 nm radiation, the UV emission of particles embedded in the biological tissue can only affect the direct vicinity of the particles. Nanocrystals of LaPO4 :Gd 3+ could, therefore, be interesting for biomedical applications such as strongly localized drug release by X-ray triggered UV uncaging reactions.